Tragic Discrimination in Hiddden Figure Movie Dialogue - Simorangkir, Imelda M.; Sofia, Yulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The movie dialogue from Hidden Figure is used in the present research. Published in 2016, this is an American motion picture. Theodore Melfi was the director of this movie. The same-titled novel served as the inspiration for this movie. The lives of three African-American women who work at NASA are chronicled in this movie. Theodore Melfi was the director of this movie.As a minority, they are positioned. By using Norman Fairlough's critical discourse theory, the researchers in the present research wanted to analyze this movie. The primary source of data for the present research is the dialogue used in the movie. The approach used to get meaning from this movie is the descriptive qualitative method. The findings from the research demonstrate that colored people in America continue to face a great deal of discrimination. However, two philosophies are represented in this movie: the philosophy of ideology of feminism.